Influence of ovarian reserves on assisted reproductive and perinatal outcomes in patients with endometriosis: a retrospective study - Liu, Shuai; Guo, Yaxin; Li, Fei; Jin, Lei (Frontiers in Endocrinology, 2023)
Objective: To investigate the association between different ovarian reserves and reproductive and adverse perinatal outcomes in patients with endometriosis. Design: Retrospective study. Setting: Reproductive Medicine Center in a hospital. Patients: Patients surgically diagnosed with endometriosis were divided into three groups according to their ovarian reserve: diminished ovarian reserve (DOR) group (n=66), normal ovarian reserve (NOR) group (n=160), and high ovarian reserve (HOR) group (n=141). Intervention(s): None. Main Outcome Measures: Live birth rate (LBR), cumulative live birth rate (CLBR), and adverse perinatal outcome for singleton live births. Results: There were significantly higher live birth and cumulative live birth rates in endometriosis patients with NOR or HOR than in those with DOR. For adverse perinatal outcomes, patients with NOR or HOR had no significant association with preterm birth, gestational hypertension, placenta previa, fetal malformation, abruptio placentae, macrosomia, or low birth weight, except for a decreased risk of gestational diabetes mellitus. Conclusion(s): Our study revealed that although patients with endometriosis with NOR and HOR had increased reproductive outcomes, patients with endometriosis with DOR had still an acceptable live birth rate and a similar cumulative live birth rate with available oocytes. Moreover, patients with NOR and HOR might not exhibit a decreased risk of abnormal perinatal outcomes, except for gestational diabetes mellitus. Multicenter prospective studies are needed to further clarify the relationship.